Answer:
We take v in the vector space V different from 0. Since v is not 0, then
[tex]< v,v>_1 \, >0 \, ;, <v,v>_2 \, >0[/tex]
Lets take k>0 such that
[tex] <v,v>_2 \, = k*\, <v,v>_1 [/tex]
Now, we take any vector w. We want to show that [tex] <v,w>_2 = k*<v,w>_1 [/tex] .
Since v is any non-zero vector, then this will prove that [tex] <a,b>_2 = k*<a,b>_1 [/tex] for any vectors a,b. The reason is that for any vector different from 0, lets name it x, there will exist a constant [tex] k_x [/tex] such that [tex] <x,y>_2 = k_x *<x,y>_1 [/tex] for any y (this is for the same reason a constant exists for v). Since y can be anything, then it can be v. But that means that [tex] k_x = k [/tex], because v also has its constant k.
Now, lets show that [tex] <v,w>_2 = k*<v,w>_1 [/tex] . Lets take a constant c such that [tex] c*<v,v>_2 = <v,w>_2 [/tex] . We have that
[tex] 0 = <v,w>_2 - c* <v,v>_2 = <v, w-cv>_2 [/tex]
Thus
[tex] <v,w-cv>_1 = 0 [/tex]
Which means that
[tex] 0 = <v,w-cv>_1 = <v,w>_1 - c<v,v>_1 [/tex]
Which means that [tex]<v,w>_1 = c<v,v>_1[/tex] . As a consequence
[tex] <v,w>_2 = c <v,v>_2 = ck*<v,v>_1 = k * <v,w>_1 [/tex]
Which proves what we were looking for.